Keanekaragaman Jenis Lamun (Seagrass) di Pesisir Pantai Desa Malanggo Pesisir Kecamatan Tinombo Selatan Kabupaten Parigi Moutong - Gafar, Moh.; Astija; Mawaddah, Hayyatun; Nurdin, Musdalifah; Febriani, Vita Indri; Febriawan, Aan (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to describe the diversity of seagrass species found on the coast of Malanggo Pesisir Village, South Tinombo District, Parigi Moutong Regency. This study used a quantitative descriptive method with a linear quadratic transect technique conducted at three observation stations. Each station was observed to determine the type and number of seagrass individuals found. The data obtained were then analyzed using the Shannon-Wiener diversity index (H’) to determine the level of seagrass species diversity at the study site. The results showed that there were five seagrass species found, namely Enhalus acoroides, Thalassia hemprichii, Halodule pinifolia, Halodule uninervis, and Cymodocea rotundata. The total number of seagrass individuals obtained was 8,548 with a diversity index value (H’) of 1.518 which is classified as moderate. This value indicates that the seagrass ecosystem in the waters of Malanggo Pesisir Village is in a relatively stable condition and is able to support the existence of several seagrass species. However, human activities around the coastal area have the potential to put pressure on the balance of the seagrass ecosystem. Therefore, efforts are needed to manage and preserve seagrass ecosystems sustainably so that their ecological function is maintained.